Distraction and Temporal Order in Narrative Situation Models. Issue 5 (4th July 2019) - Dixon, Peter; Sharma, Ana
ABSTRACT: Narrative comprehension requires the allocation of resources to the construction of a situation model describing the events and circumstances in the narrative. While mind wandering, fewer resources may be devoted to this task. In the present research, we assessed whether the effects of distraction on memory for narrative event order are qualitatively similar to those of mind wandering. In two experiments, participants read passages, sometimes with auditory noise, and after each passage rated the extent to which they were on task. Both auditory noise and spontaneous mind wandering affected temporal order judgements for narrative events. However, noise also decreased on-task rating, and temporal order memory was a linear function of on-task rating regardless of auditory noise condition. We conclude that the effects of spontaneous mind wandering and auditory noise on memory for temporal order can both be understood as a withdrawal of resources devoted to situation model construction.